Pertumbuhan Tanaman Gemitir (Tagetes erecta) Dengan Penggunaan Pupuk Organik dan Anorganik - Ida Ayu Putu Suryanti (Universitas Pendidikan Ganesha, 2019)
The purpose of this research were to determine the differences between organic and inorganic fertilizers in the growth of gemitir (Tagetes erecta) seen from the height and number of leaves. This research used a qualitative approach. This research was conducted by observing 56 fruit trees which were cultivated in two different beds and applied in organic and inorganic fertilizers at the same concentration and amount. To reduce the factors that inhibit plant growth, shade from plastic is made. Watering and maintenance were carried out every day with the same amount. Observations regarding plant height and number of leaves were carried out starting from week 1 to week 7. Data analysis was done by searching for the mean and percentage difference in yield from plant height and number of studies showing that the average plant height using organic fertilizer was 18.96 cm and organic fertilizer was 20.44 cm. This showed that there was a difference of 7.24% inorganic fertilizer higher than organic fertilizer. While the average number of leaves of gemitir plants added with organic fertilizer was 26.00 strands and inorganic fertilizers as much as 28.40 strands. The difference between the two was 8.5%, meaning that the use of inorganic fertilizers produces more leaves 8.5% or an average of 2-3 strands compared to organic fertilizers.